2010
DOI: 10.1108/09596111011035945
|View full text |Cite
|
Sign up to set email alerts
|

Staff turnover in the Greek tourism industry

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…The findings proved that younger age employees of computer graphic sectors of Karachi Pakistan may think the retention strategies for employees in different ways as compare to older age employees. Chalkiti K [16] Revealed that staff turnover levels differ across tourism jobs at various organizational levels. The study found that relative to managerial level jobs, operational level jobs also demand lower job specialization, skills and offer limited job progression opportunities.…”
Section: Previous Studies Related To Employee Turnovermentioning
confidence: 99%
“…The findings proved that younger age employees of computer graphic sectors of Karachi Pakistan may think the retention strategies for employees in different ways as compare to older age employees. Chalkiti K [16] Revealed that staff turnover levels differ across tourism jobs at various organizational levels. The study found that relative to managerial level jobs, operational level jobs also demand lower job specialization, skills and offer limited job progression opportunities.…”
Section: Previous Studies Related To Employee Turnovermentioning
confidence: 99%
“…Hypotheses formulation and testing were based on three driving pillars. First, due to operational seasonality effects in hotels and the extensive requirements to fulfil vacancies with qualified and skilful labour to work on a seasonal basis (Australia Hotel Association, 2015;Chalkiti & Sigala, 2010;Deloitte, 2015Deloitte, , 2017Goh & Lee, 2018;World Travel & Tourism Council, 2017), an emerging reality alters the need to consider the quality contribution of hospitality students during summer internships or part-time employment (H1a, H1b, H2). Students' cognitive diversity style is emerging as a critical success factor in securing service quality and organisational performance in seasonal hotels (Brevis & Vrba, 2015;Strydom & Fourie, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers such as Duro & Turrión-Prats (2019) and Ferrante et al (2018) indicate that the competitive business environment intensifies even more the subtleties of the industry's nature, including major sustainability and seasonality variables. The latter has been extensively examined due to its strong relation to service quality and organizational performance standards deviation (Chalkiti & Sigala, 2010;Goh & Lee, 2018). Furthermore, the observed seasonality problems and the high demand for labour in a relatively short period of time enabled easy labour entrance to individuals with no hospitality educational background or related professional skills to the hotel industry (Anastasiou & Koumi, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…reduced organizational commitment, staff dissonance (Treleaven and Sykes, 2005) or performance (DeLong, 2009). We also get insights into the "triggers" of knowledge leakage, such as organizational change (Treleaven and Sykes, 2005;Sitlington andMarshall, 2011), retirement (DeLong, 2009;Carmel et al, 2013) or personnel fluctuation/turnover (Acton and Golden, 2003;Chalkiti and Sigala, 2010). This highlights that the danger of knowledge leakage and possible positive or negative consequences are often found in company phases that will include change in the firms.…”
Section: Topicmentioning
confidence: 96%